FISHES - Tonny, Ganyai; Hafida, Bolhen; Jongkar, Grinang; Lee, Karen Suan Ping; Toloy Keripin, Munsang; Lee, Nyanti (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd, 2021)
The Pelagus area is located in the middle stretches of Batang Rajang, in the central part of Sarawak, under the administrative division of Kapit. The area is well-known for its long and dangerous rapids that extend for a distance of 12.8 km. Over the years, these “rapids of death” have capsized many boats along its treacherous and unpredictable waterways. To determine the fish composition in the Pelagus area, three study sectors were sampled, namely, Nanga Benin, representing the downstream area; Nanga Peraran, the midstream area; and Punan Bah, which represents the upstream areas. At each sector, sampling stations were established along the Batang Rajang and its tributaries (Fig. 1; Table 1). Field sampling was conducted in April and August of 2014, as well as January and July of 2015. Fishing methods applied include gill nets of various mesh sizes (2.5 cm, 3.81 cm, 5.08 cm, 7.62 cm and 10.16 cm), 3-layered nets, cast nets (Fig. 2–3) and electro-shocking. Similar fishing efforts were employed at the different stations (Fig. 4) and at other study sectors. Fishes caught were mostly identified in the field (Fig. 5), but others were brought to the laboratory for further study.